2001
DOI: 10.1007/s004280100483
|View full text |Cite
|
Sign up to set email alerts
|

Carcinomas of the anal canal and anal margin differ in their expression of cadherin, cytokeratins and p53

Abstract: Carcinomas of the anus are subdivided into those of the anal canal and those of the anal margin. It has been postulated that the various types of tumours of the anal canal represent a spectrum of differentiation rather than tumours of a separate origin. We compared the expression of Pan-cadherin, cytokeratins (CKs) 5/6, 7, 13, 18 and 19, p53 and MIB-1 in 17 cases of carcinoma of the anal canal and 5 cases of carcinoma of the anal margin. Expression of Pan-cadherin was decreased in 70% of carcinomas of the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…5 We found that only 4% of our much larger sample set showed TP53 mutation in the mutation cluster region (exons 5-8), and to find a significant numbers of mutations outside the cluster region would appear unlikely. We found a higher frequency of nuclear TP53 accumulation (91%) than reported previously (37-71%) 6,8 and we predict the accumulated protein in most cases would be wild type.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…5 We found that only 4% of our much larger sample set showed TP53 mutation in the mutation cluster region (exons 5-8), and to find a significant numbers of mutations outside the cluster region would appear unlikely. We found a higher frequency of nuclear TP53 accumulation (91%) than reported previously (37-71%) 6,8 and we predict the accumulated protein in most cases would be wild type.…”
Section: Discussioncontrasting
confidence: 53%
“…5 Whilst the frequency of TP53 mutation needs to be clarified, nuclear accumulation of TP53 protein has been shown in 37-71% of anal tumours. [6][7][8] Whether wild type or mutant TP53 protein can account for the observed nuclear staining is unclear.…”
mentioning
confidence: 99%
“…It is also known that loss of E-cadherin has been associated with a less differentiated phenotype of squamous cell carcinoma. [28][29][30] Altered expression of keratin genes characterized by the absence of high-molecular-weight keratins, such as K1, has previously been shown to be related to malignant growth properties. 31 The absence of keratin pearls and loss of K1 expression in tumors generated with E-cadherin-deficient II-4 cells confirmed this relationship between the concomitant loss of cellcell adhesion and differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…The altered mucosa was similar to that normally present in the anal squamocolumnar transition zone with areas akin to bronchial epithelium. Immunohistochemically, the former was CK5/6, CK7, and p63 positive, an immunophenotype described in normal anal transitional cell mucosa and carcinoma (6–8). The bronchial‐like epithelium showed a similar keratin profile, p63 positive basal cells, and was negative for thyroid transcription factor‐1 (a marker that occasionally shows basal cell nuclear positivity in typical bronchial epithelium).…”
Section: Discussionmentioning
confidence: 95%